Petrographic investigation of methane-derived authigenic carbonate crusts from Barents Sea and Norwegian Sea - Røde, Silje (UiT Norges arktiske universitet, 2016)
Methane-derived authigenic carbonate crusts from four seepage sites at the Loppa High in the southwestern Barents Sea, and one seepage site at Hola, off Vesterålen in the Norwegian Sea, have been investigated, with the main focus of understanding if and how the tests of benthic and planktonic foraminifera occurring in the crusts could serve as nucleation centers for the precipitated carbonates.